Convergent and distinctive functions of transcription factors VdYap1, VdAtf1, and VdSkn7 in the regulation of nitrosative stress resistance, microsclerotia formation, and virulence in Verticillium dahliae. (20th September 2020) - Tang, Chen; Jin, Xianjiang; Klosterman, Steven J.; Wang, Yonglin
Abstract: Reactive oxygen/nitrogen species (ROS/RNS) play a fundamental role in plant–fungal interactions. How pathogenic fungi manipulate plant‐derived ROS/RNS is of importance to the outcomes of these interactions. In this study, we explored the individual and combined contributions of three transcription factors, VdAtf1, VdYap1, and VdSkn7, in the response to ROS/RNS, microsclerotia formation, and virulence in the plant wilt pathogen Verticillium dahliae . We showed that VdYap1 is essential for ROS response. Additionally, mutants lacking any combination of the three genes shared significant hypersensitivity to nitro‐oxidative stress like sodium nitroprusside dehydrate and double deletions lacking VdYap1 and VdAtf1 resulted in further increased sensitivity to ROS. Double deletion of VdAtf1 and VdSkn7 reduced melanin production and virulence while simultaneous lack of VdSkn7 and VdYap1 disrupted nitrogen metabolism and ROS resistance. Finally, comparison of transcriptional profiles of the respective single or double mutants in response to nitro‐oxidative stress revealed that the three transcription factors are involved in denitrification of nitrated alkanes and lipids to protect against nitro‐oxidative stress. Taken together, our results demonstrate convergent and distinctive functions of VdYap1, VdAtf1, and VdSkn7 in V. dahliae, and provide new data on their roles in response to ROS/RNS in fungi. Abstract : VdYap1, VdAtf1, and VdSkn7 play convergent and distinctive roles in oxidative and nitrosative resistance, microsclerotia formation, and virulence in Verticillium dahliae .